Rare skin adverse reactions induced by osimertinib: a case report and literature review - Zhang, Ye; Ling, Mingzhu; Wang, Min; Chen, Ye; Zhang, Liting (Frontiers in Oncology, 2025)
Osimertinib is a third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) used in the treatment of EGFR mutation-positive advanced non-small cell lung cancer. Osimertinib-induced cutaneous vasculitis is a rare skin adverse reaction. We present a case study of a 49-year-old female who developed palpable purpura on her lower extremities on the 11th day of osimertinib treatment. Systemic involvement was not observed in the test results. The multidisciplinary team considered the clinical presentation of purpura as a potential case of cutaneous vasculitis. Osimertinib was immediately discontinued, and intravenous methylprednisolone along with oral cetirizine treatment was initiated. After 8 days since discontinuation of osimertinib, the patient’s skin purpura completely subsided. Subsequently, she was switched to almonertinib for treatment. We also conducted a literature review cutaneous vasculitis induced by osimertinib and other EGFR-TKIs. We hope to provide some safety alert information for clinical practice and recommend enhanced monitoring during the medication process.